2020
DOI: 10.1097/meg.0000000000001878
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of combined therapy radiofrequency ablation/transarterial chemoembolization versus transarterial chemoembolization/radiofrequency ablation on management of hepatocellular carcinoma

Abstract: Background One of the most widespread cancer-associated death worldwide is Hepatocellular carcinoma. Concerning hepatic malignant tumor staging system known as Barcelona clinic of liver cancer, a superior curative response could be carried out by combined techniques [radiofrequency ablation (RFA) and transarterial chemoembolization (TACE)] for stage B comparing with TACE alone as palliative monotherapy. Objectives To discuss the merging effect of RFA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Very limited data are available on the combination of TA followed by TACE. One clinical study was found comparing TA + TACE with TACE + TA by El Dorry et al and they found median disease-free survival of 17.1 months for TACE + TA vs 23.2 months for TA + TACE (p > 0.05) [12]. These results confirm our results as no statistical differences were found.…”
Section: Discussionsupporting
confidence: 90%
“…Very limited data are available on the combination of TA followed by TACE. One clinical study was found comparing TA + TACE with TACE + TA by El Dorry et al and they found median disease-free survival of 17.1 months for TACE + TA vs 23.2 months for TA + TACE (p > 0.05) [12]. These results confirm our results as no statistical differences were found.…”
Section: Discussionsupporting
confidence: 90%